A Comparison of Symptoms, Functional Status and Quality of Life by the Survivor Stages of Pancreatic Cancer Patients (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to identify the difference of symptoms, functionalstatus and quality of life (QOL) according to the survival stage of pancreatic cancer patients.Method/Statistical analysis: Descriptive, cross-sectional design. A sample of 139 patients was surveyed.The participants were as patients who were diagnosed with pancreatic cancer in Republic of Korea. The datacollected was analyzed with descriptive statistics.Findings: Nausea and vomiting symptoms were significantly higher in acute survival stage than in extendedsurvival stage and insomnia and diarrhea were significantly higher in extended survival stage than in acutesurvival stage functional status and QOL were significantly higher in extended survival stage than in acutesurvival stage.Improvements/Applications: The differences in symptoms, functional status and QOL by the survivalstage of pancreatic cancer patients were grasped and the empirical evidence was given for performingdifferentiated nursing interventions by each survival stage.